Coffee Leaves Valorization through a Metabolomic Approach - Davide Rovelli; Ada Nucci; Bianca Serito; Chiara Dall’Asta (Proceedings)
Coffee by-products, such as coffee leaves, are components of the coffee plant that remain underexplored. In recent years, driven by efforts from both the public and private sectors to pursue circular economy goals, there has been a resurgence in the interest in coffee leaves for producing new products and diversifying the coffee supply chain. It is well known that coffee waste is a source of bioactive compounds and secondary metabolites, which have various applications in the food and beverage sector for producing functional food ingredients and nutraceuticals. Recently, coffee leaf infusions have been approved as novel food in the European Union, demonstrating the feasibility of marketing coffee leaves. To support their potential applications, it is essential to thoroughly understand the chemical composition and phytochemical profile of the by-product to guide future investigations. Omics techniques can be used to support the valorization process, collecting a large amount of information from a complex matrix allowing the use of coffee by-products as extraction materials for the discovery and recovery of functional compounds. The simultaneous extraction of polar and non-polar fractions and the subsequent application of liquid chromatography coupled with high- or low-resolution mass spectrometry techniques allows the simultaneous identification and quantification of several compounds through a holistic approach. Moreover, through the application of chemometrics on the spectral information, it is possible to highlight the main similarities or differences in the batch that could change according to their origin or the post-harvest process as well as discover new molecules with bioactive properties. The application of omics techniques provides support for the reintegration of coffee by-products back into the production chain, reducing the impact on the environment, providing new business opportunities for farmers and companies.